2006
DOI: 10.1097/01.paf.0000233550.07598.56
|View full text |Cite
|
Sign up to set email alerts
|

Massive Pulmonary Embolization by Cerebral Tissue After Head Trauma in an Adult Male

Abstract: We report a case of an adult man who was run over by a car, suffering severe head trauma. After 3 hours in the hospital, he experienced sudden and severe hemodynamic deterioration, dying immediately. The autopsy showed massive cerebral tissue pulmonary embolization (CTPE), confirmed by immunohistochemistry. Multiple fractures of the skull, tear of the transverse sinus, and brain laceration of the occipital lobe were present. CTPE is very infrequent. In children and adults, it occurs as a complication of severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Based on previous case reports and summarized reviews, we found 39 reported cases of CTPE after severe head trauma. [2][3][4][5][6][7][8][9][10][11][12][13][14] For instant deaths in these cases, the victims were 47 years or younger (Table 1), whereas in our case, the victim was 65 years old (the eldest case of CTPE with instant death). The younger ages in these reported cases may relate to better cardiac health.…”
mentioning
confidence: 95%
“…Based on previous case reports and summarized reviews, we found 39 reported cases of CTPE after severe head trauma. [2][3][4][5][6][7][8][9][10][11][12][13][14] For instant deaths in these cases, the victims were 47 years or younger (Table 1), whereas in our case, the victim was 65 years old (the eldest case of CTPE with instant death). The younger ages in these reported cases may relate to better cardiac health.…”
mentioning
confidence: 95%